Regulation of Na+/H+ exchangers, Na+/K+ transporters, and lignin biosynthesis genes, along with lignin accumulation, sodium extrusion, and antioxidant defense, confers salt tolerance in alfalfa - Rahman, Md Atikur; Woo, Jae Hoon; Lee, Sang-Hoon; Park, Hyung Soo; Kabir, Ahmad Humayan; Raza, Ali; El Sabagh, Ayman; Lee, Ki-Won (Frontiers in Plant Science, 2022)
Accumulation of high sodium (Na+) leads to disruption of metabolic processes, and decline in plant growth and productivity. Therefore, current study was undertaken to clarify how Na+/H+ exchangers, and Na+/K+ transporters genes contribute to Na+ homeostasis, and substantial involvement of lignin biosynthesis genes in salt tolerance in alfalfa (Medicago sativa L.) that is poorly understood. In this study, high Na+ exhibited a substantial reduction of morpho-physiological indices, and induced oxidative stress indicators in Xingjiang Daye (XJD; sensitive genotype), while Zhongmu (ZM; tolerant genotype) remained unaffected. The higher accumulation of Na+ and lower accumulation of K+, and K+/(Na++K+) ratio were found in roots and shoots of XJD compared to ZM under salt stress. The ZM genotype showed high expression of SOS1 (salt overly sensitive 1), NHX1 (sodium/hydrogen exchanger 1) and HKT1 (high affinity potassium transporter 1), which were involved in K+ accumulation, and excess Na+ extrusion from the cells compared to XJD. The lignin accumulation was higher in salt adapted ZM genotype than sensitive XJD genotype. Consequently, several lignin biosynthesis-related genes including 4CL2, CCoAOMT, COMT, CCR, C4H, PAL1 and PRX1 exhibited higher mRNA expression in salt tolerant ZM compared to XJD. Moreover, antioxidant enzymes (CAT, SOD, APX, and GR) activity was higher in of ZM relative to XJD. This result suggests that high antioxidant provided the defense against oxidative damages in ZM, while low enzyme activity with high Na+ triggered the oxidative damage in XJD. These findings together illustrate the ion exchanger, antiporter, and lignin biosysthetic genes involving mechanistic insights into differential salt tolerance in alfalfa.